Preliminary Study of Solar PV and Hydrogen Fuel Cell Generator for Isolated Power Systems in Indonesia - B., Muhammad Siddiq; Akbar , Wahyu Eko Prasetyo; Juangsa, Firman Bagja (ITB Graduate School Conference, 2025)
The urgency to reduce carbon emissions in Indonesia has accelerated the transition from fossil fuels to New and Renewable Energy (NRE), especially in isolated power system areas that still rely on Diesel Power Plants (PLTD). This study explores the feasibility of a hybrid Solar Photovoltaic (PV) and Hydrogen Fuel Cell Generator (HFCG) system to provide sustainable electricity for isolated power systems. A case study was conducted in Werinama, Maluku, using HOMER Pro for modelling and optimization. Results show that the proposed PLTS-HFCG system achieves a Levelized Cost of Electricity (LCOE) of 0.208 USD/kWh (3.425 IDR/kWh), which is more economical than the current diesel-based cost of 0.265 USD/kWh (4.367 IDR/kWh). In addition to economic advantages, the system offers zero-emission power generation. This preliminary study serves as an initial reference for adopting hydrogen-based renewable energy systems in remote regions of Indonesia.